The Influence Of Health Education Using Video On Knowledge About Menarche - Riau Roslita; Ivo Cahyang Rubichan; Vella Yovinna Tobing (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
Menarche is the first menstruation experienced by girls, usually at ages 11-14 years. Girls need special attention to address pre-pubertal issues, especially lack of knowledge about menarche. This lack of knowledge triggers negative responses when facing the first menstruation. The solution is health education using animated video media. This study aims to analyze differences in knowledge levels among fifth-grade female students who have not yet experienced menarche, before and after health education intervention on menarche. The sample consists of 30 respondents using purposive sampling technique. The study employs a quantitative method with a pre-experimental one-group pretest-posttest design. Data analysis uses paired t-test to compare pretest and posttest results. The results show a significant difference in knowledge before (pretest mean score 62.35) and after (posttest 86.47) education. Bivariate analysis with paired t-test yields a p-value of 0.001, indicating a significant effect of health education on children's knowledge about menarche. The study hopes audiovisual media becomes an option to improve girls' knowledge, so they better understand menarche and prevent health issues like urinary tract infections